Can probiotics prevent diarrhoea in an 18 month-old boy who is treated with antibiotics? A Critical Appraisal of a Topic - Biharie, Anand (Student Undergraduate Research E-journal!, 2016)
Diarrhoea is a common side effect in children on an antibiotic treatment. Antibiotic-associated diarrhoea can cause serious adverse effects such as dehydration and electrolyte disturbances, resulting in possible hospitalisation. This critical appraisal of a topic is focused on the question whether probiotics can prevent antibiotic associated diarrhoea in an 18 month-old boy. Four randomised controlled trials with a strong validity demonstrated the benefit of probiotics. Children that took probiotics in addition to antibiotics had a lower incidence of diarrhoea then children that took a placebo. Also, other positive effects of probiotics, concerning diarrhoea, were found.